Becoming Researchers: Making Academic Kin in the Chthulucene. (20th April 2018) - Verlie, Blanche; Emery, Sherridan; Osborn, Maia; Beasy, Kim; Coleman, Bianca; Kezabu, Kevin; Nicholls, Jennifer
Abstract: Graduate students are often plagued by stress and anxiety in their journeys of becoming researchers. Concerned by the prevalence of poor graduate student wellbeing in Australia, we share our experiences of kin-making and collaboration within #aaeeer (Australasian Association for Environmental Education Emerging Researchers), a collective of graduate students and early career researchers formed in response to the Australian Association for Environmental Education (AAEE) conference in Hobart, Tasmania, in 2014. In this article, we begin to address the shortage of research into graduate student wellbeing, led by graduate students. Inspired by Donna Haraway's work on making kin in the Chthulucene, we present an exploration that draws together stories from the authors about the positive experiences our kin-making collective enables, and how it has supported our wellbeing and allowed us to work collaboratively. Specifically, we find that #aaeeer offers us a form of refuge from academic stressors, creating spaces for 'composting together' through processes of 'decomposing' and 'recomposing'. Our rejection of neoliberal norms has gifted us experiences of joyful collective pleasures. We share our experiences here in the hope of supporting and inspiring other emerging and established researchers to 'make kin' and challenge the potentially isolating processes of becoming researchers.